ANALYSIS OF THE INFLUENCE OF EWOM, PROMOTION AND EASE OF USE OF DISNEY+ HOTSTAR SERVICES ON SUBSCRIPTION DECISIONS IN JAKARTA CITY - Supiani Supiani; Sonia Miranda (Asosiasi Dosen Muda Indonesia, 2023)
The purpose of this study was to analyze the effect of EWOM, Promotion and Ease of Use on Disney+ Hotstar Subscription Decisions. To obtain all the data needed, the researchers used Primary Data, namely by using an Online Questionnaire. The analytical method in this study used quantitative primary data, the test stages carried out were: Test Validity, Reliability, Normality, Multicollinearity, Heteroscedasticity, t test, F test, Multiple Linear Regression and Coefficient of Determination. The data used in this study used a questionnaire instrument, and 100 respondents collected valid data. The sampling method in this study was Non-Probability Sampling with Purposive Sampling technique. The testing tool used is SPSS Ver 25. The results showed that (1) EWOM and Ease of Use have no partial effect on Subscription Decisions (2) Promotion has a partial effect on Subscription Decisions (3) EWOM, Promotion and Ease of Use have an effect simultaneously on purchasing decisions.